2013
DOI: 10.1590/s1519-99402013000300017
|View full text |Cite
|
Sign up to set email alerts
|

Biometric hoof evaluation of athletic horses of show jumping, barrel, long rope and polo modalities

Abstract: This study aimed to evaluate, through biometry, the forelimb hoof of horses participating in show jumping, barrel, long rope and polo competitions. Thirty subjects were assessed in relation to each competition (total of 120 animals). The linear measurements (cm) included the dorsal length of the toe; medial and lateral lengths of the quarter; medial and lateral heights of the quarter; lateral and medial lengths of the heel; medial and lateral heights of the heel; hoof length; hoof width; frog length; and frog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Changes in toe angle can be described using the equation: toe angle = 56.587303 + 0.1663238 × month -0.1388137 (month -3.74569)2, R²=0.04, P≤0.01. Similar results have been reported in Dutch Warmblood foals (KROEKENSTOEL et al, 2006), adult Criollo horses (CANTO et al, 2006), and Polo horses (SAMPAIO, 2013). Although,' there was no significant interaction between toe angle and toe length, HINTZ (1983) andGLADE andSALZMAN (1985) reported that a low hoof angle positively influenced hoof growth.…”
Section: Resultssupporting
confidence: 78%
“…Changes in toe angle can be described using the equation: toe angle = 56.587303 + 0.1663238 × month -0.1388137 (month -3.74569)2, R²=0.04, P≤0.01. Similar results have been reported in Dutch Warmblood foals (KROEKENSTOEL et al, 2006), adult Criollo horses (CANTO et al, 2006), and Polo horses (SAMPAIO, 2013). Although,' there was no significant interaction between toe angle and toe length, HINTZ (1983) andGLADE andSALZMAN (1985) reported that a low hoof angle positively influenced hoof growth.…”
Section: Resultssupporting
confidence: 78%
“…This slight difference might be due to the manner of trimming, interval of trimming, the farrier and also the type of work carried out by the animal. According to Sampaio et al (2013), a shorter toe length theoretically accelerates the limb dynamics, but it can also be related with wall fragility or excessive trimming.…”
Section: Resultsmentioning
confidence: 99%
“…Biometrics are linear or angular measures that characterize a component's shape and can be expressed in terms of the variation modes of the SSM. We consider biometrics for the hoof capsule, the third phalanx ( 7 11 ), the third metacarpal, the first and second phalanx ( 12 ), and the distal sesamoid bone. The definitions of the selected biometrics are tabulated in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A standard procedure in morphological studies of equine distal limb anatomical structures focuses on one-dimensional linear or angular measures, such as hoof angle, hoof length, medial-lateral width of the phalanges, and so on, or two-dimensional measures, such as the joint surface. They are measured from radiographs ( 7 , 8 ), MRI data ( 9 ), photographs ( 8 , 9 ), or from in-situ measurements in vivo ( 10 , 11 ) or post-mortem ( 12 ).…”
Section: Introductionmentioning
confidence: 99%